A cafeteria diet modifies the response to chronic variable stress in rats. (March 2013) - Zeeni, N.; Daher, C.; Fromentin, G.; Tome, D.; Darcel, N.; Chaumontet, C.
<x xml:space="preserve">Abstract</x> Stress is known to lead to metabolic and behavioral changes. To study the possible relationships between stress and dietary intake, male Sprague-Dawley rats were fed one of three diets for 6 weeks: high carbohydrate (HC), high fat (HF), or "Cafeteria" (CAF) (Standard HC plus a choice of highly palatable cafeteria foods: chocolate, biscuits, and peanut butter). After the first 3 weeks, half of the animals from each group (experimental groups) were stressed daily using a chronic variable stress (CVS) paradigm, while the other half of the animals (control groups) were kept undisturbed. Rats were sacrificed at the end of the 6-week period. The effects of stress and dietary intake on animal adiposity, serum lipids, and corticosterone were analyzed. Results showed that both chronic stress and CAF diet resulted in elevated total cholesterol, increased low-density lipoprotein (LDL), and lower high-density lipoprotein (HDL). In addition, increases in body weight, food intake, and intra-abdominal fat were observed in the CAF group compared with the other dietary groups. In addition, there was a significant interaction between stress and diet on serum corticosterone levels, which manifest as an increase in corticosterone levels in stressed rats relative to non-stressed controls in the HC and HF groups but not in the CAF group. These results show that a highly palatable diet, offering a choice of food items, is associated with a reduction in the response to CVS and could validate a stressor-induced preference for comfort food that in turn could increase body weight.